2015
DOI: 10.1016/j.ultrasmedbio.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Synthetic Aperture Harmonic Imaging for Scanning Focal Malignant Liver Lesions

Abstract: Abstract-The purpose of the study was to perform a clinical comparison of synthetic aperture sequential beamforming tissue harmonic imaging (SASB-THI) sequences with a conventional imaging technique, dynamic receive focusing with THI (DRF-THI). Both techniques used pulse inversion and were recorded interleaved using a commercial ultrasound system (UltraView 800, BK Medical, Herlev, Denmark). Thirty-one patients with malignant focal liver lesions (confirmed by biopsy or computed tomography/magnetic resonance) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The proposed assessment methodology is based on earlier publications of studies of clinical evaluation between pairs of sequences [24]- [26] and suggested testing procedures according to recommendation 500 from ITU-R [27] for subjective quality assessment. The proposed methodology describes two assessment situations, one for the assessment of diagnosticaccuracy and one for diagnostic-thinking.…”
Section: Assessment Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…The proposed assessment methodology is based on earlier publications of studies of clinical evaluation between pairs of sequences [24]- [26] and suggested testing procedures according to recommendation 500 from ITU-R [27] for subjective quality assessment. The proposed methodology describes two assessment situations, one for the assessment of diagnosticaccuracy and one for diagnostic-thinking.…”
Section: Assessment Methodologymentioning
confidence: 99%
“…15 seconds on average per image sequence. The details of the study and the statistical analysis is presented in [26].…”
Section: Phase IIImentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, SAI allows for higher resolution and interpretability throughout the entire image, rather than only at prespecified foci. SAI has shown superior image quality in breast, 25 liver, 26 abdominal US imaging 27 due to increased resolution.…”
Section: Synthetic Aperture Imagingmentioning
confidence: 99%